Magnetic Carbon Nanotubes/Graphene Oxide Nanocomposites: One-Step Controllable Production, and Their Excellent Microwave Absorption Capabilities - Wu, Mei; Qi, Xiaosi; Xie, Ren; Qin, Shuijie; Deng, Chaoyong; Zhong, Wei (Frontiers in Materials, 2020)
In this research, three-dimensional (3D) hierarchical networks of magnetic carbon nanotubes/graphene oxide (CNTs/GO) nanocomposites (NCs) were synthesized by a one-step hydrothermal method with the idea of constructing more interface contacts, double loss mechanism and synergy effect. The obtained results showed that the content of NCs gradually transitioned from CoCO3 to CoxFe3-xO4. And CoCO3-CoxFe3-xO4/CNTs/GO quaternary NCs and CoxFe3-xO4/CNTs/GO ternary NCs could be selectively synthesized when the Co:Fe molar ratio decreased from 1:1 to 1:3. The as-prepared samples displayed excellent microwave absorption properties (MAPs) in terms of the minimum reflection loss (RLmin) and the corresponding absorption bandwidth (FBcor) with the reflection loss values lower than -10 dB. The RLmin and large FBcor values for the as-prepared samples were -54.69 dB and 2.36 GHz, -63.99 dB and 2.48 GHz, -63.36 dB and 2.68 GHz, respectively. The designed 3D hierarchical networked structure of magnetic GO/CNTs NCs displayed outstanding comprehensive MAPs, which could deliver a practical and effective strategy to develop high-performance microwave absorbers, taking into account their low cost, lightweight, and high stability.